Knowledge Level And Mother's Attitude Related To Stunting In Infants Aged 6-23 Months : Tingkat Pengetahuan dan Sikap Ibu Berhubungan dengan Kejadian Stunting pada Bayi Usia 6-23 Bulan - Wuwuh Ambarwati; Aprianti (Universitas Airlangga, 2022)
Background: Kebumen Regency is a stunting locus district in 2021, with a stunting prevalence of 12.13%. Indirect causes of stunting, including variables that can be intervened for stunting prevention. Objective: The purpose of this study was to ascertain how the prevalence of stunting relates to knowledge, attitudes, and feeding behaviors in infants aged 6-23 months at the Padureso Primary Health Care, Kebumen Regency. Methods: Quantitative research using a case-control study design matching variables for average birth weight and birth length > 47 cm. The population is 356 mothers of babies. The sample size using Lemeshow obtained a total sample of 33 mothers with stunting babies and 33 mothers with non-stunted babies using the cluster sampling technique. Chi-Square test data. Results: The majority of respondents aged 31-40 are 53%, with a basic education level of 56.1%, and most mothers do not work 93.9%. The findings of the bivariate test revealed a connection between knowledge (p values ​​= 0.026, OR = 3.077) and attitudes (p-value = 0.013, OR = 3.538) with the incidence of stunting. There is no association between feeding practices and the incidence of stunting (p-value = 0.618) Conclusions: Mothers of infants aged 6-23 months are expected to increase knowledge about complete nutrition further and improve attitudes regarding the provision of a variety of foods so that the practice of feeding babies follows the nutritional needs of babies.